The Role of Work Ethics in Mediating the Effect of Religiosity and Commitment on Work Quality A Case Study: Baitul Maal wat Tamwil in Brebes and Pubalingga Regencies - Syah, Toufan Aldian (Wealth: Journal of Islamic Banking and Finance, 2023)
The research aims to determine the effect of religiosity and commitment on employee work ethic, then the effect of religiosity, commitment, and work ethic on work quality and the effect of religiosity on work quality through work ethic and the effect of commitment on work quality through the work ethic of Islamic Savings and Loans and Financing Cooperatives (KSPPS ) Baitul Maal wat Tamwil in the South Central Java Region with a focus on research locations in Brebes Regency and Purbalingga Regency. This research is a quantitative study with 56 BMT employees in Brebes and Purbalingga Regencies. The data collection uses a questionnaire tested for validity and reliability, while the data analysis uses SEM-PLS analysis using Smart-PLS 3.2.9 software. After analyzing the data, several conclusions were obtained: (1) religiosity and commitment have a positive effect on employee work ethic; (2) religiosity and work ethic have a positive effect on the quality of employee work; (3) commitment does not affect the quality of employee work; (4) work ethic is proven to have a role as a mediating variable on the effect of religiosity on work quality; (5) work ethic is proven to have a role as a mediating variable on the effect of commitment to the work quality.